Kesenjangan Antara Perencanaan Dan Implementasi Program Pemerintah Daerah: Review Literatur Tentang Lemahnya Monitoring Dan Evaluasi Berbasis Kinerja - Muhammad Al Habib; Sufian Hamim; Raden Imam Al Hafis (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The gap between planning and implementation remains a critical issue in local government program management. Many regional agencies already have planning documents, performance indicators, reporting systems, and evaluation mechanisms, yet these instruments do not always ensure that programs are implemented according to targets and produce measurable results. This article aims to analyze the pattern of gaps between planning and implementation of local government programs by positioning performance based monitoring and evaluation as the critical point. This study uses a literature review method involving 20 scientific articles and a document review of 2 official documents from the Office of Industry, Trade, Cooperatives, Small and Medium Enterprises of Riau Province. The analysis classifies findings into several themes, namely performance planning, program implementation, organizational capacity, reporting systems, digitalization, and performance evaluation. The findings show that program gaps are not only caused by weak planning, but also by limited human resource capacity, weak coordination, fragmented performance data, and evaluation practices that remain largely administrative. Monitoring and evaluation have not fully functioned as mechanisms for correction, organizational learning, and program control. This article concludes that improving local government program implementation requires stronger outcome indicators, integrated data, tiered monitoring, substantive internal evaluation, and the use of evaluation results as a basis for program improvement.